Localization of aquaporin-5 in sweat glands and functional analysis using knockout mice - Song, Yuanlin (Blackwell Science Inc, 2002)
Sweat secretion involves the transport of salt and water into the lumen of the secretory coil of the sweat gland. By analogy to salivary and submucosal glands, where fluid secretion is aquaporin-5 (AQP5) dependent, we postulated that aquaporin water channels might facilitate sweat secretion. Immunolocalization with specific antibodies revealed strong expression of AQP5 at the luminal membrane of secretory epithelial cells in sweat glands in mouse paw skin. Novel quantitative methods were developed to compare sweat secretion in wild-type mice and mice lacking AQP5. Total hindpaw sweat secretion was measured by proton nuclear magnetic resonance of sweat-derived (1)H(2)O in (2)H(2)O solvent, and sweat secretion from individual glands was measured by real-time video imaging of sweat droplet formation under oil. Sweat secretion rates after pilocarpine stimulation did not differ in wild-type mice (0.21 ± 0.03 nl min(−1) gland(−1)) vs. mice lacking AQP5 (0.19 ± 0.04 nl min(−1) gland(−1)). The lack of effect of AQP5 on sweat secretion rate was confirmed by microcapillary collections of sweat from defined regions of mouse paws. Also, as by direct counting of droplets, the number of functional sweat glands was not affected by AQP5 deletion. Sweat gland morphology was similar in wild-type and AQP5 null mice. From sweat coil geometry and gland secretion rate, the rate of fluid secretion was estimated to be 130 nl min(−1) cm(−2) of secretory epithelium, substantially lower than that of > 500 nl min(−1) cm(−2) in kidney proximal tubules and salivary glands, where active fluid absorption or secretion is aquaporin dependent. These results indicate the expression of AQP5 in sweat gland secretory epithelium, but provide direct evidence against its physiological involvement in sweat fluid secretion in mice.